1999
DOI: 10.1152/ajprenal.1999.277.1.f130
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase in the JGA of the SHR: expression and role in tubuloglomerular feedback

Abstract: The spontaneously hypertensive rat (SHR) has an enhanced tubuloglomerular feedback (TGF) and a diminished buffering by juxtaglomerular apparatus (JGA)-derived NO. We examined the hypothesis that these effects are due to decreases in nitric oxide synthase (NOS) expression or limited availability of l-arginine or tetrahydrobiopterin (BH4). SHR had significantly ( P < 0.05) greater mRNA abundance (by RT-PCR) or protein (by Western analysis) for neuronal NOS (nNOS, or type I) and endothelial cell NOS (ecNOS, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…The administration of 7-NI did not change TGF response in the hydronephrotic animals, whereas in the controls, increased reactivity and sensitivity were observed. This diminished role of NO from nNOS in blunting of TGF is also seen in SHR (59). Conversely, during intratubular infusion of L-arginine, decreased reactivity and sensitivity of the TGF were only determined in hydronephrotic animals.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The administration of 7-NI did not change TGF response in the hydronephrotic animals, whereas in the controls, increased reactivity and sensitivity were observed. This diminished role of NO from nNOS in blunting of TGF is also seen in SHR (59). Conversely, during intratubular infusion of L-arginine, decreased reactivity and sensitivity of the TGF were only determined in hydronephrotic animals.…”
Section: Discussionmentioning
confidence: 76%
“…However, micropuncture experiments (41) showed that the tubuloglomerular feedback (TGF), which is an important mechanism in the control of GFR and blood pressure regulation, is reset during volume expansion in a paradoxical way to a much higher sensitivity and activity in the hydronephrotic kidney. The regulation of the sensitivity and reactivity of the TGF is intimately coupled to NO production in the macula densa (4) and the same kind of TGF resetting has been described in animal models for hypertension (11,49,59).NO is synthesized from a family of NO synthases [neuronal NO synthase (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS)] that utilize L-arginine as a substrate (48). Most evidence indicates that NO production is reduced in renal disease (1).…”
mentioning
confidence: 99%
“…The L-arginine/NO pathway is upregulated in SHR, with higher vascular endothelial NOS (eNOS) and renal iNOS protein mass than in WKY rats and increased nitrate plus nitrite (NO x ) excretion directly after weaning at 3-4 wk, the so-called prehypertensive stage (146). In SHR, renal cortical and macula densa nNOS levels are increased (154), and NO production by vascular smooth muscle iNOS is enhanced (160). In the brain in SHR, the NOS system is programmed differently than in other tissues.…”
Section: Inappropriate Activation Of the Renin-angiotensin-aldosteronmentioning
confidence: 99%
“…Enhanced tubuloglomerular feedback may contribute to high blood pressure. In animal models of genetic hypertension, tubuloglomerular feedback is enhanced (53,54), and resetting of tubuloglomerular feedback may also contribute to salt-sensitive hypertension in humans (1,23,38).…”
mentioning
confidence: 99%